Lise Meitner : a life in physics - Sime, Ruth Lewin, 1939- (California studies in the history of science, 1996)
Lise Meitner (1878-1968) was a pioneer of nuclear physics and co-discoverer, with Otto Hahn and Fritz Strassmann, of nuclear fission. Braving the sexism of the scientific world, she joined the prestigious Kaiser Wilhelm Institute for Chemistry and became a prominent member of the international physics community. Of Jewish origin, Meitner fled Nazi Germany for Stockholm in 1938 and later moved to Cambridge, England. Her career was shattered when she fled Germany, and her scientific reputation was damaged when Hahn took full credit-and the 1944 Nobel Prize-for the work they had done together on.